The effect of phonated breathing on oxygen uptake during and after submaximal cycling - Nejka Potočnik; Kaja Stanković (ANNALES ZRS, Scientific Publishing House of ZRS Koper, 2022)
Purpose: Positive expiratory pressure (PEP) exhalation during exercise is reported to improve body adaptation to exercise and enhance the exercise tolerance in patients with chronic obstructive pulmonary disease. Wearing mouthguards results in lower oxygen consumption and increased performance by increasing PEP in athletes. Airway resistance during expiration can be manipulated by phonation. Thus, the aim of our study was to examine the effects of phonated breathing on cardiopulmonary adaptation to moderate exercise and subsequent recovery. Methods: 26 young healthy participants conducted the same moderate steady cycling protocol using three different breathing patterns: spontaneous breathing (BrP1), phonated breathing pronouncing the sound "h" (BrP2) and phonated breathing pronouncing the sound "sh" (BrP3). Heart rate, oxygen consumption, CO2 production, respiratory rate, tidal volume, respiratory exchange ratio and ventilatory equivalents were measured (Cosmed, Italy) before, during and 20 minutes after cycling. Data were analyzed using SPSS, with significance level p<0.05. Results: The analysis revealed no significant differences related to the breathing economy; respiratory rate was increased, and tidal volume decreased with spontaneous breathing compared to both phonated breathing patterns during exercise; no effect of BrPs on cardiopulmonary parameters was found in recovery. Conclusion: Our results do not confirm the assumption that PEP breathing improves exercise economy probably because of the low exercise intensity applied. Further studies should be conducted at higher exercise loads or in patients with pulmonary dysfunction.